DAMPAK AKTIVITAS MENDENGARKAN TERHADAP KUALITAS HUBUNGAN INTERPERSONAL PERTEMANAN SEBAYA - Ni Wayan Pande Putri Yudhani (2021)
In communication interactions, there is listening activity, where these activities occur in every level of society and are intertwined with various relationships, one of which is interpersonal relationships. We often encounter this interpersonal relationship in various kinds, one of which is in the scope of peer friendship. This illustrates that listening is found in the interaction of interpersonal relationships in peers. This study aims to determine whether or not there is an impact on listening activities and how much the impact affects interpersonal relationships among peers. The Uncertainty Reduction Theory explains how communication is used to reduce uncertainty between people involved in conversations so that interpersonal relationships can work well. This research uses explanative quantitative research methods and data collection techniques using survey methods by distributing questionnaires to 99 research respondents. To determine the effect and magnitude of the influence of the two variables, the researcher used the Spearman Rank correlation test analysis using the Product And Service Solution (SPSS) Windows version 25. This means that there is an influence or impact on listening activities on the quality of peer interpersonal relationships.